Efficacy and safety of rituximab given at 1, 000 mg on days 1 and 15 compared to the standard regimen to treat adult immune thrombocytopenia. Issue 10 (3rd September 2013) - Mahévas, Matthieu; Ebbo, Mikael; Audia, Sylvain; Bonnotte, Bernard; Schleinitz, Nicolas; Durand, Jean‐Marc; Chiche, Laurent; Khellaf, Medhi; Bierling, Philippe; Roudot‐Thoraval, Françoise; Godeau, Bertrand; Michel, Marc
<x xml:space="preserve">Abstract</x> Rituximab (RTX) is used off‐label to treat immune thrombocytopenia (ITP) but the regimen now commonly used in rheumatoid arthritis has not been evaluated in ITP. The aim of this large French multicenter retrospective study was to compare the efficacy and safety of two RTX regimens in adult's ITP. The efficacy of two (RTX) regimens: standard therapy of 375 mg/m2 weekly for 4 weeks vs. a rheumatoid arthritis (RA) regimen of 1, 000 mg on days 1 and 15, to treat ITP was compared. We included adults patients with previously primary ITP treated with RTX instead of treated primary ITP. (CR) was defined as a platelet count >100 × 109/L, and a response (R) by a platelet count of >30 × 109/L with a least a doubling of the baseline value. Of the 107 patients included, 61 (57%) received the standard regimen and 46 (43%) the RA regimen. Baseline characteristics and overall response rates at 3 month (M3) and 12 months (M12) were not significantly different between the groups. At M12, 22/61 patients (36%) treated with the standard regimen and 23/46 (50%) with the RA regimen achieved an overall response (R + CR). The initial pattern of response at M3 was associated with a later pattern of response by M12 in both groups. In multivariate analysis, both a younger age and a low number of previous therapies were associated with a higher likelihood of overall response at M12. Tolerance was good and comparable between the two groups. The RA regimen is an effective and safe alternative to the standard regimen to treat adults with ITP. Am. J. Hematol. 88:858–861, 2013. © 2013 Wiley Periodicals, Inc.